The hadiths that were declared weak by Al-Hafiz Al-Sakhawi (d. 902 AH) in his book Al-Qawl Al-Badi’ fi Al-Salawa Ala Al-Habib Al-Shafi’ (may God be pleased with him) (College of Basic Education Research Journal, 2025)
This research included a study of three hadiths out of a total of nine hadiths that Al-Hafiz Al-Sakhawi (d. 902 AH) - may God Almighty have mercy on him - expounded in his book The Wonderful Saying in Praying for the Beloved Intercessor (may God Almighty bless him and grant him peace), where he - may God Almighty have mercy on him - exalt the first hadith with a composition. The chain of transmission of a hadith on the basis of another hadith, and the second hadith was attributed to the disagreement of one of its narrators from the Companions - may God be pleased with them -, and the third hadith was attributed to the illusion of one of its narrators, by making it from the chain of transmission of another companion.